State Apparatus Neutrality in Electoral Governance: The Siyasah Tanfidziyah Perspective on Oversight Frameworks in Indonesia - Wulan Maulidia Putri; Fathul Mu’in; Alan Yati (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
State apparatus neutrality is a constitutional principle central to the integrity of electoral governance in democratic states governed by the rule of law. This article examines the implementation of Article 4 of Bawaslu Regulation No. 6 of 2018 concerning the supervision of neutrality of the State Civil Apparatus (ASN), the Indonesian National Armed Forces (TNI), and the Indonesian National Police (Polri) in West Tulang Bawang Regency. Using a qualitative socio-legal approach, the study integrates doctrinal legal analysis with empirical field research. The framework of siyāsah tanfīdhiyyah is employed as a normative–analytical instrument grounded in the principles of amānah, justice (al-‘adl), accountability (mas’ūliyyah), and oversight (al-raqābah). The findings indicate that, while supervisory mechanisms comply procedurally with regulatory standards, their substantive effectiveness is constrained by fragmented sanctioning authority, limited institutional capacity, uneven internalization of neutrality norms, and entrenched informal power relations. The article argues for an integrative governance approach that combines regulatory coherence, institutional effectiveness, and ethical internalization of public authority.